2000
DOI: 10.4049/jimmunol.164.12.6550
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Migration Through Monolayers of Endothelial Cell Lines Involves VCAM-1 Signaling Via Endothelial Cell NADPH Oxidase

Abstract: Lymphocytes migrate from the blood across endothelial cells to reach foreign substances sequestered in peripheral lymphoid organs and inflammatory sites. To study intracellular signaling in endothelial cells during lymphocyte migration, we used murine endothelial cell lines that promote lymphocyte migration and constitutively express VCAM-1. The maximum rate of resting splenic lymphocyte migration across monolayers of the endothelial cells occurred at 0–24 h. This migration was inhibited by anti-VCAM-1 or anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

23
329
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(357 citation statements)
references
References 83 publications
23
329
0
4
Order By: Relevance
“…Many investigations have shown that ROS produced by leukocyte NADPH oxidase modulate the expression of adhesion molecules involved in leukocyte trafficking [13,14]. Recently, an intriguing report showed that activation of NADPH oxidase is required for VCAM-1-dependent lymphocyte migration [23]. NO synthesis is catalyzed by isoforms of NO synthase expressed in leukocytes, endothelial cells and various other cells [24].…”
Section: Discussionmentioning
confidence: 99%
“…Many investigations have shown that ROS produced by leukocyte NADPH oxidase modulate the expression of adhesion molecules involved in leukocyte trafficking [13,14]. Recently, an intriguing report showed that activation of NADPH oxidase is required for VCAM-1-dependent lymphocyte migration [23]. NO synthesis is catalyzed by isoforms of NO synthase expressed in leukocytes, endothelial cells and various other cells [24].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, OS increased mRNA levels of NOX2 and NOX1, and monocyte adhesion was shown to be blocked by siRNA against NOX1. Interestingly, Matheny et al have shown that VCAM-1 ligand binding induced ROS generation via NADPH oxidases in endothelial cells and promoted lymphocyte migration by actin restructuring in endothelial cells (278). Inhibiting NADPH oxidase activity with DPI or Apocynin blocked lymphocytic migration across mouse endothelial cells to greater than 65% (278).…”
mentioning
confidence: 99%
“…In addition to a4b1 integrin, VCAM-1 can bind other integrins, including a4b7, adb2, aMb2, and a9b1 (23)(24)(25)(26)(27)(28). It is known that a4b1 integrin binds Ig-like domains 1 and 4 (29)(30)(31)(32), and that activated integrins are necessary for firm leukocyte adhesion to the endothelium via Ig-like domains 1 and 4 of VCAM-1 (33).…”
mentioning
confidence: 99%